Acculturation of hygiene norms among immigrants to Sweden - Krueger, Joel; Eriksson, Kimmo; Hazin, Isabela; Tibajev, Andrey; Strimling, Pontus (Frontiers in Psychology, 2023)
Hygiene norms in Sweden are generally loose compared to most other countries. Does this looseness affect the hygiene norms among people who immigrate to Sweden from other countries? In a study of hygiene norms among immigrants to Sweden, the change in physical environment and material living conditions, acculturation to Swedish culture and norms, and selection effects were all expected to lead immigrant hygiene norms to be closer to Swedish looseness. However, in a sample of 447 immigrants from 12 different countries, immigrants reported hygiene norms that were even stricter than those found in their countries of origin. We propose an explanation based on a combination of uncertainty about prevailing hygiene norms and the social risk and stigma associated with being perceived as unhygienic. We conclude that acculturation processes may rely on mechanisms that are domain specific.